Civismo popular, algazarra nas ruas: comemorações da independência nacional na Bahia - Wlamyra Albuquerque (IdeAs)
The article is about the public celebrations for the independence of Brazil that have taken place in Bahia since July 2, 1823, when the Portuguese troops were forced out of the country by the Bay of All Saints. It is a civic-popular calendar that has as its high point the parade through the streets of Salvador, the Bahian capital, and in other cities of the Recôncavo, with students, representatives of native communities, social movements, political parties, capoeiristas, sambistas, military corporations, cultural associations and religious brotherhoods. The main elements of the parade are two sculptures, the Caboclos. The Caboclo is the representation of a native pointing a spear and crushing a dragon with his feet, which would be the colonial submission. The Cabocla, on the other hand, is the representation of Catarina Paraguassú, the Tupinambá native who married the Portuguese explorer Diogo Alvares Correia, during the colonial period. She parades heavily adorned and carrying the flags of Bahia and Brazil. Both are also venerated in candomblé, a religion of African origin. The objective of the text is to highlight the historical and cultural dynamics that, intertwined in this national mythology, continue to be fundamental to analyze political projects, popular aspirations and social tensions that, throughout two hundred years, mark the trajectory of independent Brazil. The sources that support this text are official documents, press, police correspondence, chroniclers, and artists.